Fatal Escherichia coli skin and soft tissue infections in liver transplant recipients: report of three cases. Issue 2 (26th December 2012) - Janny, S.; Bert, F.; Dondero, F.; Nicolas Chanoine, M.‐H.; Belghiti, J.; Mantz, J.; Paugam‐Burtz, C.
Abstract Gram‐negative bacilli are unusual agents of skin and soft tissue infections. Most previous cases have been reported in cirrhotic or immunocompromised patients, including a single case in a liver transplant recipient. The present report describes 3 cases of fatal skin or soft tissue infections caused by Escherichia coli that occurred in the postoperative course of liver transplantation. The 3 patients were profoundly immunosuppressed as a result of pre‐transplant cirrhosis and the postoperative administration of a potent immunosuppressive therapy. Skin and soft tissue infections developed within the first week after liver transplantation, while graft liver function was satisfactory. The 3 patients presented with fever and skin lesions with or without bullae. Despite prompt appropriate antibiotic therapy and surgical debridement, the outcome was rapidly fatal (24 h on average). E. coli was isolated from subcutaneous tissues in 2 cases and from several blood cultures in the third one. The 3 isolates belonged to distinct phylogenetic groups, and did not harbor most of the virulence factors usually reported in extraintestinal pathogenic E. coli isolates. Our report suggests that E. coli can cause severe skin or soft tissue infection in the postoperative course of liver transplantation. The onset of infection is very early and the outcome is extremely poor, despite prompt adapted medical and surgical treatment. Host factors, rather than E. coli bacterial virulence potential, appear to be the major determinants of severity in these patients.